Can Personality Factors and Body Esteem Predict Imagery Ability in Dancers? - Dagmara Budnik-Przybylska; Maria Kaźmierczak; Jacek Przybylski; Maurizio Bertollo (MDPI AG, 2019)
Dancing is mainly regarded as a form of art, which has been linked to the expression of emotions. Imagery is a well-known technique for enhancing performance. Additionally, specific personality traits are likely to facilitate performance. In the dancer's performance, regarding the body as a tool is crucial. The following study examines personality and perceived body esteem as predictors of imagery ability in professional dancers. We analyzed two experimental groups, namely ballet dancers and professional dancers of other styles, and a control group. A sample of 249 people took part in the study: 155 women and 94 men aged 18-56 years. Participants filled in The Imagination in Sport Questionnaire and Polish adaptations of the Big Five Inventory-Short and the Body Esteem Scale. Results indicated that while each experimental group differed significantly from the control group in terms of their imagery ability, there were no differences between the two experimental groups. Findings revealed that personality traits, mainly higher openness to experience, and body esteem, mainly related to physical condition, were significant predictors of higher imagery ability in all groups.